Interaction between the genomes of Lactococcus lactis and phages of the P335 species - Kelly, William J.; Altermann, Eric; Lambie, Suzanne C.; Leahy, Sinead C. (Frontiers in Microbiology, 2013)
Phages of the P335 species infect Lactococcus lactis and have been particularly studied because of their association with strains of L. lactis subsp. cremoris used as dairy starter cultures. Unlike other lactococcal phages, those of the P335 species may have a temperate or lytic lifestyle, and are believed to originate from the starter cultures themselves. We have sequenced the genome of L. lactis subsp. cremoris KW2 isolated from fermented corn and found that it contains an integrated P335 species prophage. This 41 kb prophage (Φ KW2) has a mosaic structure with functional modules that are highly similar to several other phages of the P335 species associated with dairy starter cultures. Comparison of the genomes of 26 phages of the P335 species, with either a lytic or temperate lifestyle, shows that they can be divided into three groups and that the morphogenesis gene region is the most conserved. Analysis of these phage genomes in conjunction with the genomes of several L. lactis strains shows that prophage insertion is site specific and occurs at seven different chromosomal locations. Exactly how induced or lytic phages of the P335 species interact with carbohydrate cell surface receptors in the host cell envelope remains to be determined. Genes for the biosynthesis of a variable cell surface polysaccharide and for lipoteichoic acids (LTAs) are found in L. lactis and are the main candidates for phage receptors, as the genes for other cell surface carbohydrates have been lost from dairy starter strains. Overall, phages of the P335 species appear to have had only a minor role in the adaptation of L. lactis subsp. cremoris strains to the dairy environment, and instead they appear to be an integral part of the L. lactis chromosome. There remains a great deal to be discovered about their role, and their contribution to the evolution of the bacterial genome.